Konflik Sunni-Syiah dan dampaknya terhadap komunikasi intra-religius pada komunitas di Sampang-Madura - Rachmah Ida; Laurentius Dyson (Masyarakat, Kebudayaan dan Politik, 2015)
The conflict between the Muslim Sunni and Shia, hereafter Sunni-Shia conflict, occurred in Sampang on August 2012 was recognised as a group identity conflict. The existence of Muslim Shia community as minority amongst the Sunni majority in Madura has long become the latent intra-faith clash in this Island. This study explores the socio-cultural and political aspects of Sunni-Shia conflict in Sampang District of Madura and examines the views of these two communities about their religius stance, values, and socio-cultural practices in their places, and how they have perceived other religius group identity regarded as distinct to each other. Methods applied for this study are qualitative survey using two approaches i.e. socio-cultural historic and inter-cultural communication. The data were gathered through depth interviews, observations, and secondary documentations sourced from media news and articles, government policy and relevant literatures. This study found that the root of the conflict was begun from the familial (brotherhood) clash, which then extended into the clash between Sunni and Shia communities and the issue of religius ideology and identity. The difference on their opinion, perception, and attitude of the Sunni and Shia groups have become the key issues of these two groups to fight their religius identities interest and their beief upon the true of Islam according to their version. As a result, their intra-religius life and communication between these two groups have become paralised and stucked.